Living on the edge of America : at home on the Texas-Mexico border - Maril, Robert Lee (Texas A & M University Press, 1992)
On the southern edge of America a diverse group of people lead ordinary lives in rather extraordinary circumstances. Mexican Americans, Anglos, and Mexican nationals meet there, in the subtropical beauty of the Rio Grande Valley and amid conditions of extreme poverty and social inequality, and create a distinctive blend of cultures, languages, and attitudes toward life. The stories that emerge are stories of individual victories, daily standoffs, and brutalizing defeats.
Keywords: Lower Rio Grande Valley (Tex.) -- Rural conditions -- Case studies.; Mexican Americans -- Texas -- Lower Rio Grande Valley -- Social conditions -- Case studies.; Mexicans -- Texas -- Lower Rio Grande Valley -- Social conditions -- Case studies.; White people -- Texas -- Lower Rio Grande Valley -- Social conditions -- Case studies.; Basse vallée du Rio Grande (Tex.) -- Conditions rurales -- Études de cas.; Américains d'origine mexicaine -- Texas -- Basse vallée du Rio Grande -- Conditions sociales -- Études de cas.; Mexicains -- Texas -- Basse vallée du Rio Grande -- Conditions sociales -- Études de cas.; Personnes blanches -- Texas -- Basse vallée du Rio Grande -- Conditions sociales -- Études de cas.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Mexican Americans -- Social conditions; Mexicans -- Social conditions; Rural conditions; White people -- Social condition; Texas -- Lower Rio Grande Valley; Case studies